Data analytics and digital learning as tools for decision- making in scientific and technological research institutions - Sámano Castillo, José (2024)
The results obtained from the design and implementation of an indicator system are presented in this document. This system analyzes the information from a responsive platform that displays the technological, research, and human resources training potential of the 493 national laboratories, university laboratories, and support units of the National Autonomous University of Mexico (UNAM). The performance indicator system uses the platform's database to monitor, analyze, and reveal the advantages achieved over time. It incorporates a cutting-edge business intelligence and analytics tool: Microsoft PowerBI®, which allows for advanced visualization, segmentation, KPIs, interactive graphs with depth and aggregation levels, key statistics, and optimization. The system is responsive for five categories: capabilities, equipment, personnel, communication, and forecasts. It includes 45 simple KPIs and a section for forecasts (machine learning) to leverage the information generated in the last seven years.